Microfinance Management System: Human Resource II: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Human resource II is the system that is required to manage and retain the records andinformation of every employee in the organization in order to keep track of every employee inan organization's workforce. Especially when it comes to human resource activities such ascollecting employee information and ensuring that it is stored in a private and secure location;not only that, but in terms of having a step-by-step process for employees, let's say they workfor one company; that company is responsible for securing information and processingaccurate details, especially when it comes to PERFORMANCE, salaries, and payrolls. Exactdates for processing leaves and payments, as well as an accurate time for everyone workingin that company's time in and time out.The results of this study and system are remarkable. It has resulted in an accurate timesheetfor each employee, ensuring that the proper salary is calculated based on the person's job andthe number of days worked. This system has also shortened the time it takes to complete keyemployee-related tasks, such as payroll and other financial transactions. Moreover, it hasverified that the employee's information is secure and safe from illegal access. Moreover,because all data is recorded in the system, it has made it easier to process staff departuresand vacations. This study and system have had a significant impact on how corporationsmanage employee-related tasks.Our research project will discuss and focus on Microfinance Human Resource II, a newly high-tech system that can help and improve companies' procedures in terms of their employees,and we will make sure that this research and system meet the standard in terms of integration,testing, troubleshooting, process, and deliverables.
Keywords: IT & Management